The Relationship Between Academic Stress and Class XII Students' Biology Learning Outcomes - Yunita Amelia; Supriyatin Supriyatin; Rusdi Rusdi; Lili Akhmad (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2023)
Learning outcomes are the important matter in the learning process so that learning outcomes are often used as a determinant of success in achieving learning purposes. The learning outcomes achieved by each student will be different. This is due to several factors, one of which is related to student psychological conditions in the form of stress in an academic context. This study aims to determine the relationship between academic stress and biology learning outcomes of class XII students. The research was conducted at SMA Negeri 4 Bekasi City in the 2022/2023 academic year. The method used is a quantitative descriptive method with correlational studies. The sample used was 104 students of class XII who were selected through simple random sampling technique. The instruments used were questionnaires and multiple choice test questions. The prerequisite test results show that the data are normally distributed and homogeneous. The result of calculating the correlation coefficient is -0.473 and is included in the medium criteria. Thus, it can be concluded that there is a significant negative relationship between academic stress and the biology learning outcomes of class XII students. The higher the academic stress, the lower the biology learning outcomes of class XII students. The coefficient of determination is 0.224, which means that academic stress contributes 22.4% to the biology learning outcomes of class XII students.